Nagel's Criticism Of Physicalism - Thomas W. Smythe; Thomas Evans (European Scientific Journal, ESJ, 2016)
The philosopher Thomas Nagel is well known for being skeptical of the claim that psychological states are purely physical. When physical science gives us a complete description of the world, it leaves out the point of view from which each of us is aware of their perspective on the world. This paper is a critical treatment of Nagel's problem with physicalism. We ignore the vast literature on the self.